Trends and Patterns of Top Ten Common Cancers in Eastern India from 2014 to 2021: A Retrospective Hospital-based Cancer Registry Data Update - Shraddha Raj; Dinesh K. Sinha; Richa Madhawi; Seema Devi; Kunal Kishor; Rajesh K. Singh; Aman Prakash (Indian Journal of Community Medicine, 2024)
Background: India is a vast and diverse country with existing variations in the frequency and distribution of cancers across its various parts. In regions lacking population-based cancer registries (PBCRs) in a vast country like India, hospital-based cancer registry (HBCR) data become an important source of information on the trends and patterns of a region. To determine the numerical trends of cases of the top ten cancer sites reporting to HBCR of a tertiary care cancer center in Bihar from 2014 to 2021. Materials and Methods: The details of all histopathologically confirmed cancer cases registered in the HBCR department of radiation oncology, State Cancer Institute, Indira Gandhi Institute of Medical Sciences, Patna, India between January 2014 and December 2021 were included in this retrospective observational study. All these cases were grouped site-wise and listed in descending order of the total number of cases reported in each group. Cross-tabulation with age and sex distribution was done. The frequency distribution of the top ten leading cancers for every consecutive calendar year was plotted in line diagrams for time trend analysis. Statistical Package for the Social Sciences (IBM SPSS Statistics for Windows, Version 20.0. Armonk, NY: IBM Corp.). was used for analysis. Annual percent change (APC) was determined for the number of cases of all ten cancer sites using joinpoint regression analysis (Joinpoint Regression Software, Version 4.0.4—May 2013; Statistical Methodology and Applications Branch, Surveillance Research Program of the US National Cancer Institute; Bethesda, MD, USA). Results: Out of 32,057 total cancer cases registered between Jan 2014 and Dec 2021, 21,848 patients (68.2%) cases constituted the top ten cancers. The top ten cancers among both sexes were cancer gallbladder (n = 4204, 13.1%), head and neck (n = 3395, 10.6%), breast (n = 3392, 10.6%), lung (n = 2069, 6.5%), cervix (n = 2039, 6.4%), hematolymphoid (n = 1930, 6.0%), liver (n = 1572, 4.9%), stomach (n = 1116, 3.5%), ovary (n = 1103, 3.4%), and colon-rectum (n = 1028, 3.2%). Except for cervical and hematolymphoid cancers, the rest all showed a rising trend over consecutive years. Conclusion: Cancer of the gallbladder continues to be among the most common cancers in the region. Focused research in all aspects of this deadly disease is needed. Strengthening of prevention and screening programs for common cancers and upliftment of the existing infrastructure for diagnosis and treatment of cancer in the region are necessitated.